Effect of platelet-rich plasma versus steroid injection in plantar fasciitis: a randomized clinical trial - Rachit Sharma; Narendra Kumar Chaudhary; Mandeep Karki; Dev Ram Sunuwar; Devendra Raj Singh; Pranil Man Singh Pradhan; Prakash Gyawali; Sailendra Kumar Duwal Shrestha; Kailash Kumar Bhandari (BMC Musculoskeletal Disorders, 2023)
Abstract Background Plantar fasciitis (PF) is a common orthopaedic problem, with heel pain worsening the quality of life. Although steroid injection is often used if the conservative treatment fails, Platelet-Rich Plasma (PRP) injection is gaining popularity due to its safety and long-lasting effect. However, the effect of PRP versus steroid injection in PF has not been studied yet in Nepal. Therefore, this study aimed to assess the effect of PRP compared with steroid injection in the treatment of PF. Methods This study was a single-center, hospital-based, open-label, parallel-group randomized clinical trial to compare the effect of PRP injection with steroid injection in plantar fasciitis between August 2020 and March 2022. A total of 90 randomly selected participants aged 18 to 60 years suffering from plantar fasciitis with failed conservative treatment were intervened. The American Orthopaedic Foot and Ankle Society (AOFAS) and the Visual Analog Scale (VAS) scoring system were used to evaluate functional mobility and pain before and after the intervention for three and six months, respectively. Statistical analyses were performed using a Student’s two-sample t-test. P-value < 0.05 was considered statistically significant. Results The PRP injection showed a better outcome than the steroid injection in six months follow-up. The mean (± SD) VAS score was significantly decreased in the PRP group (1.97 + 1.13) than in the steroid group (2.71 ± 0.94) with the group difference of -0.73 (95% CI: -1.18 to -0.28) at six months. Similarly, there was a significant increase in the AOFAS scores in the PRP group (86.04 ± 7.45) compared to the steroid group (81.23 ± 9.60) at six months of follow-up with a group difference of 4.80 (95% CI: 1.15 to 8.45). There was also a significant reduction of plantar fascia thickness in the PRP group compared to that of the steroid group (3.53 ± 0.81 versus 4.58 ± 1.02) at six months of follow-up with the group difference of -1.04 (95% CI: -1.44 to -0.65). Conclusion The PRP injection showed better outcomes than steroid injection in plantar fasciitis treatment over the course of six months. Further research with a larger population and longer follow-up than six months is needed to generalize the findings and their long-term efficacy. Trial registration NCT04985396. First registered on 02 August 2021. ( https://clinicaltrials.gov/ct2/show/NCT04985396 )